An integrative approach to ancient agricultural terraces and forms of dependency: the case of Cutamalla in the prehispanic Andes - Mader, Christian; Godde, Philipp; Behl, Martin; Binder, Christoph; Hägele, Elena; Isla, Johny; Leceta, Fernando; Lyons, Mike; Marsh, Erik; Odenthal, Rachel; Fernengel, Emilia; Stryjski, Paul; et al. (Frontiers in Environmental Archaeology, 2024)
This paper presents an integrative and interdisciplinary approach to the study of ancient agricultural terraces and food production systems. Our approach consists of (1) a resource dependency theoretical framework and (2) the application of a variety of archaeological and geoscientific methods, including archaeological and geomorphological surveys, archaeological excavations, drone surveys, mapping based on satellite imagery and high-resolution digital elevation models (DEMs), geographic information system (GIS) applications, soil testing, phytolith analysis, radiocarbon dating, and calculations of food supply capacity and labor requirements. We apply these to the prehispanic site of Cutamalla (3,300 m asl) in the southern Peruvian Andes, which serves as an ideal and pioneering case study. Previous research has focused primarily on the settlement of Cutamalla, particularly through large-scale archaeological excavations, but less attention has been paid to the extensive farming terraces surrounding the settlement and the close relationship between agricultural and settlement activities. By analyzing both the terrace and settlement levels, we take a new perspective and introduce the term agricultural terrace-settlement system for such complexes. Our results show that the residential occupation of Cutamalla and the use of the surrounding farming terraces coincided: the agricultural terrace-settlement system was intensively used for a relatively short period of about 200 years (~250–40 BCE) during the Formative Late Paracas and transitional Initial Nasca periods, long before the famous Inka terrace agricultural systems. There is no evidence of reoccupation of the site and subsequent reuse of the agricultural system. Our data also document the large extent of agricultural terraces around Cutamalla (221 ha) and that maize was likely a major crop grown there. Finally, we place these findings in their broader socio-economic and ecological context. Cutamalla was an important regional center and economic hub during a very dynamic period characterized by significant population growth and increased violence. Not only a more humid climate, but probably also forced collective labor were cornerstones of substantial agricultural production in Cutamalla and the region.